PENENTUAN SEGMENTASI YANG MENDUKUNG STRATEGI PEMSARAN UNTUK TRANSAKSI BISNIS DI INTERNET - Natsir, Muh (Universitas Muhammadiyah Magelang, 2010)
Determination of market segmentation within a company can not be saparated from the information and data that go through a variety of ways. The management company should have its own compartment undeer departement R & D as a special unit to follow up of various complaints and suggestions relating to improvement of the underlying strategy to the saisfacion of consumer behavior. Intrnet facility with devices supporting the technology enables the development of management information systems. Marketing startegies adopted should be trailored to the company's internal and external conditions, in this case, consumers and other outsiders. This article will discuss about: